Performance analysis of a modified ejector-enhanced auto-cascade refrigeration cycle. (15th February 2023) - Liu, Shuilong; Bai, Tao; Wei, Yuan; Yu, Jianlin
Abstract: In this paper, a modified ejector-enhanced auto-cascade refrigeration cycle with R290/R170 is proposed on the basis of a basic ejector-enhanced auto-cascade refrigeration cycle proposed previously. An additional expansion valve and internal heat exchanger are utilized in the modified cycle and are located after condenser. Refrigerant leaves condenser with smaller quality and then is throttling in expansion valve. Thus, the quality at inlet of separator can be adjusted to meet varying refrigeration capacity as varying ambient temperature. The thermodynamic analyses based on energy and exergy methods are conducted to compare the performances of two cycles. The influences of several critical operating parameters on cycle performances are investigated in detail. The results indicate that the modified cycle can obtain higher COP under the given operating conditions than the basic cycle. The modified cycle presents average improvement of 7.52%–8.86% in COP and 9.28%–11.33% improvement in volumetric refrigeration capacity. Besides, the exergy destruction of condenser, ejector and expansion valves in modified cycle is much less than that in basic cycle. The total exergy destruction of the modified cycle is decreased by 6.65%–8.35%, and exergy efficiency is increased by 7.54%–8.85%. Therefore, the modified cycle shows its energy-saving advantage and application potential in low-temperature refrigeration. Highlights: >A modified ejector-enhanced auto-cascade refrigeration cycle is proposed. >Comparisons between MEARC and BEARC is performed based on energy and exergy methods. >Less exergy destruction of condenser, ejector and expansion valves can be achieved in MEARC. >8.86% and 8.85% improvements in COP and exergy efficiency can be obtained in the MEARC.